2006
DOI: 10.1111/j.1600-0447.2006.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice and schizophrenia: a review of the ‘mental illness is an illness like any other’ approach

Abstract: An evidence-based approach to reducing discrimination would seek a range of alternatives to the 'mental illness is an illness like any other' approach, based on enhanced understanding, from multi-disciplinary research, of the causes of prejudice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
366
6
21

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(415 citation statements)
references
References 149 publications
(209 reference statements)
22
366
6
21
Order By: Relevance
“…Not only has the social model of disability been criticised for failing to take into account issues of embodiment and emotionality (Shakespeare and Watson, 2002), it also poses additional challenges when transposed to the mental health field. The mental health survivor/user movement has never fully accepted that 'mental illness' can be justly compared to physical 'impairment' and recent research suggests that the 'mental illness is like any other illness' approach actually does little to address stigma and discrimination (Read et al, 2006). 'Experiential' rights-based claims problematise a purely 'social model of disability' because people who seek to extricate themselves from prevailing bio-medical definitions of 'psychosis' cannot readily mobilise this model to assert the uniqueness of particular 'extra-ordinary experiences', which, it is argued, requires particular expression and an appreciation of its meaningfulness (Plumb, 1994;Plumb, 2002).…”
Section: The Policy Framework: Recovery and Inclusionmentioning
confidence: 99%
“…Not only has the social model of disability been criticised for failing to take into account issues of embodiment and emotionality (Shakespeare and Watson, 2002), it also poses additional challenges when transposed to the mental health field. The mental health survivor/user movement has never fully accepted that 'mental illness' can be justly compared to physical 'impairment' and recent research suggests that the 'mental illness is like any other illness' approach actually does little to address stigma and discrimination (Read et al, 2006). 'Experiential' rights-based claims problematise a purely 'social model of disability' because people who seek to extricate themselves from prevailing bio-medical definitions of 'psychosis' cannot readily mobilise this model to assert the uniqueness of particular 'extra-ordinary experiences', which, it is argued, requires particular expression and an appreciation of its meaningfulness (Plumb, 1994;Plumb, 2002).…”
Section: The Policy Framework: Recovery and Inclusionmentioning
confidence: 99%
“…Herewith, the risk of biological reductionism increases 41 , a belief commonly associated with dehumanizing feelings about individuals with mental disorders 38,42,43 . Thus, recently graduated psychiatrists could use a strict-biological misconception of mental illness to serve as an intellectual resource for stigma [44][45][46][47] . In the same way, psychiatric university hospitals would hold a better comprehension of the scientific advances on brain biology, with those working there demonstrating consequently less social distance.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the many studies finding that use of the label increases negative attitudes (Read et al 2006) research repeatedly demonstrates that beliefs about the causes of schizophrenia play a significant role in stigmatizing attitudes. The most recent review found that in 28 of 31 studies bio-genetic causal beliefs are related to negative attitudes and that in 24 of 26 studies psycho-social causal beliefs were related to positive attitudes (Read et al in press).…”
Section: Forummentioning
confidence: 99%
“…However, evidence suggests that the majority of people who receive the diagnosis (Dudley et al 2009), like family members and the general public (Read et al 2006), view the causes of psychosis, as being predominantly of psychosocial origin. The heterogeneity within the population who receive a diagnosis of schizophrenia would suggest that there will be multiple aetiological pathways that incorporate many such factors, and preliminary evidence suggests that many service users find labels that allow for this (such as traumatic psychosis and drug-induced psychosis) may be more acceptable (Kingdon et al 2008).…”
Section: Forummentioning
confidence: 99%